The Study of Wall Painting of Ani Monuments in the Late 19th – Early 20th Century - Makarova, Anna L. (Actual Problems of Theory and History of Art, 2023)
The article presents a survey of all published information about the paintings of medieval Ani from the documents of the expeditions of the Imperial Archaeological Commission led by Nikolai I. Marr (1892–1893 and 1904–1917), which are still the most significant and large-scale ones in the history of the study of that ancient city. The materials left by N. I. Marr and his staff are the most important and sometimes the only sources of knowledge about the painting of Ani churches. The text of the article is divided into paragraphs devoted to the study of the paintings of the churches of St. Gregory (of Tigran Honents), St. Gregory (Bakhtagek or Khachut), and the Savior (Prkchi), as well as of the rock tomb of Tigran Honents. The careful study of the sources and locations of unpublished materials on the painted ensembles of Ani lays the foundation for further research, including the study of archival documents, conducting in situ examination of paintings, and a comprehensive art historical analysis. Based on the current research about Byzantine monumental painting, involving an in-depth understanding of artistic communications within the medieval world, it seems possible to view the paintings of Ani in the most reliable historical perspective. The study was supported by the Russian Science Foundation (Project No. 22-18-00354, https://rscf.ru/project/22-18-00354 “The Architecture and monumental art of Ani as a phenomenon of world artistic culture. Making of the metropolitan school of Armenian architecture of the 10th–14th centuries”), at the National Research Moscow State University of Civil Engineering.